Acute Airway Compromise After Isolated Mandibular Subcondyle Fracture in a Patient With a Hemi-Mandible: A Case Report. (3rd August 2021) - Pyfer, Bryan James; Cason, Roger William; Mundy, Lily; Powers, David Bryan; Erdmann, Detlev
Evaluation of the airway is the first step in any trauma protocol, and this is particularly important in instances of facial trauma. While airway compromise is not uncommon in blunt or penetrating facial trauma, it is rarely a significant concern in instances of an isolated mandibular fracture. We report a rare case of immediate airway compromise in an elderly, edentulous female who sustained an isolated mandibular subcondyle fracture, complicated by her history of a remote hemimandibulectomy for management of her oral cancer. Initial airway management was performed conservatively with prone or lateral positioning under continuous pulse oximetry monitoring in the intensive care unit, followed promptly by open anatomic reduction and internal fixation of the fracture under more optimal operative conditions. After stabilizing the subcondylar fracture, the patient followed a mechanical soft/no-chew diet for 6 weeks until the fracture was healed. She has experienced no airway concerns since her surgery. This case report stresses the importance of a comprehensive evaluation of the airway in facial trauma patients with altered baseline anatomy, as well as highlights the considerations for emergent surgical airway versus immediate or delayed surgical fracture fixation.